THE IMPACT OF AI TOOLS (E.G., CHATGPT) ON DEVELOPING STUDENTS’ WRITING SKILLS IN ESL CLASSROOMS IN UZBEKISTAN - Xudayberganova Ro’za Rasul qizi (TADQIQOTLAR, 2026)
This article investigates the influence of Artificial Intelligence (AI) tools, specifically ChatGPT, on the development of writing skills among ESL (English as a Second Language) students in Uzbekistan. The study analyzes how AI tools affect grammatical accuracy, vocabulary acquisition, and structural organization of texts. The findings indicate that while the strategic integration of AI can enhance academic performance and student confidence, it simultaneously poses challenges related to academic integrity and the potential decline of critical thinking. The research provides pedagogical recommendations for EFL/ESL instructors in the local context.